Challenges of Blended Learning in Refugee Camps: When Internet Connectivity Fails, Human Connection Succeeds - Dridi, Mohamed Aziz; Radhakrishnan, Dhinesh; Moser-Mercer, Barbara; DeBoer, Jennifer (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
In this paper, we studied the implementation of a course on global history as a blended section of a massive open online course (MOOC) and the learning challenges faced by the students in three crisis contexts: Azraq refugee camp (Jordan), Kakuma refugee camp (Kenya), and Amman urban refugee center (Jordan). The results showed that poor Internet connection in the camps severely impacted both students’ and instructors’ experience of the course. In the context of chronic Internet connectivity issues, the instructors had difficulties assessing their students’ needs and challenges. The results also showed that in light of these intermittent connection problems, the collaborative learning environment helped students navigate the challenges of a blended course. Also, the onsite visit by the online tutors and the face-to-face interactions that resulted from it had a noticeable impact on the human dynamics of the course by allowing instructors to provide targeted solutions to students’ problems as well as by building rapport between the students and the instructional team.